Numerical studies of the efficiency of binary geothermal power plants at the studied thermal fields of Russia - Stanislav A. Yankovsky; Alexandr S. Zavorin; Natalia S. Yankovsky; Svyatoslav A. Tsibulskiy (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. The necessity to develop the technologies in Russia that use non-traditional energy sources. The formation of these technologies will allow providing energy resources to the population without harmful emissions into the environment. Aim. Comprehensive analysis of the operating characteristics of a binary geothermal power plants in various climatic operating conditions. Objects. Thermal diagrams of binary geothermal power plants applicable to installation in different geographic regions and operation from different geothermal sources. Methods. Numerical studies based on mathematical algorithms of binary geothermal plant systems, comparative analysis of the efficiency of binary geothermal plants based on various external parameters. Results and conclusions. Numerical studies have been conducted to determine the efficiency of geothermal power plants with a binary thermal circuit and an air-cooled condenser were conducted during their operation on various sources, for which 15 known geothermal sources located in Russia in different geographical regions were selected. Possible operating parameters of binary geothermal power plants were analyzed based on the known characteristics of the fluid at the well outlet. Since the geothermal power plant has an air-cooled condenser in its thermal circuit, its operating parameters were obtained from the average monthly ambient air temperatures in the calendar year in the region where the analyzed geothermal source is located. Numerical studies showed the impact of thermal source parameters and climatic features on the efficiency of electric energy generation by means of a binary plant. It was revealed that with the possible operation of a binary geothermal plant during a calendar year, the highest average monthly electric power is expectedly achieved in the cold period of time, in this case in January, and is 1752 kW for the Mogoysky hot spring. For the warmest month of the year – July – the binary power plant of the Mechigmen hot spring could have the greatest electric power of 930 kW. The greatest absolute electric efficiency in January reaches 15.22%, depends to a greater extent on the value of the temperature of the heat supply in the cycle and among the binary stations considered in this work, the geothermal power plants in the settlement of Chazhemto could have it.